Preparation, characterization, in vitro drug release and anti-inflammatory of thymoquinone-loaded chitosan nanocomposite - Mothanna Sadiq Al-Qubaisi; Ashwaq Shakir Al-Abboodi; Fatah H. Alhassan; Samer Hussein-; Moayad Husein Flaifel; Eltayeb E.M. Eid; Hussah Abdullah Alshwyeh; Mohd Zobir Hussein; Sulaiman Mohammed Alnasser; Mohammed Ibrahim Saeed; Abdullah Rasedee; Wisam Nabeel Ibrahim (Elsevier, 2022)
In this study, we formulated Thymoquinone-loaded nanocomposites (TQ-NCs) using high-pressure homogenizer without sodium tripolyphosphate. The TQ-NCs were characterized and their anti-inflammatory determined by the response of the LPS-stimulated macrophage RAW 264.7 cells in the production of nitric oxide, prostaglandin E2, tumor necrosis factor-α, interleukin-6, and interleukin-1β. The physicochemical properties of TQ-NC were determined using different machines. TQ was fully incorporated in the highly thermal stable nanoparticles. The nanoparticles showed rapid release of TQ in the acidic medium of the gastric juice. In medium of pH 6.8, TQ-NC exhibited sustained release of TQ over a period of 100 h. The results suggest that TQ-NC nanoparticles have potential application as parenterally administered therapeutic compound. TQ-NC effectively reduce production of inflammatory cytokines by the LPS-stimulated RAW 264.7 cells, indicating that they have anti-inflammatory properties. In conclusion, TQ-NC nanoparticles have the characteristics of efficient carrier for TQ and an effective anti-inflammatory therapeutic compound.